2005
DOI: 10.1111/j.1467-8535.2005.00501.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the medium effect in computer‐aided assessment of school Chemistry and college Computing national examinations

Abstract: This article presents results of a comparison between paper and computer tests of ability in Chemistry and Computing. A statistical model is employed to analyse the experimental data from almost 200 candidates. It is shown that there is no medium effect when specific traditional paper examinations in Chemistry and Computing are transferred into electronic format. The effect of rewording for computer-delivered test questions is also investigated and again the conclusion is that no evidence of a difference could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 10 publications
5
10
0
Order By: Relevance
“…However this difference did not affect the test results significantly. This result supports findings of Ashton [14] which they could not find any evidence of either medium or rewording effect on test mode.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…However this difference did not affect the test results significantly. This result supports findings of Ashton [14] which they could not find any evidence of either medium or rewording effect on test mode.…”
Section: Discussionsupporting
confidence: 94%
“…The results of this study supports the results of several studies which have found no significant difference on students' scores in CBT and P&P testing environments, [6]- [14], and [28].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…However, the proctored nature of the assessments should be noted here, whereas the present study is particularly concerned with unproctored online contexts, such as was used by Hewson et al (2007), which have been understudied to date. Other authors have also noted a lack of modality effects when comparing proctored, computerized course-based assessments with pen and paper administrations (e.g., Ashton, Beevers, Korabinski, & Youngson, 2005;Cassady & Gridley, 2005). Kingston (2009) reviewed 81 studies (all of which seemed to have used a proctored in-class setting), comparing computer-and paperadministered MCQ tests, in schools rather than higher education settings, and concluded that only very small effect sizes have been observed in these studies overall.…”
Section: Investigations Of Modality Effects In a Course-based Assessmentmentioning
confidence: 99%
“…As part of PASS-IT the effect of the delivery medium was investigated in the unit assessments in other subject areas -those of Higher Chemistry and Higher National Certificate (HNC) in Computing. Performance data was gathered from 137 Higher Chemistry students, and 44 Higher National Computing students, and the statistical analysis of this data was carried out using a general linear model, taking into account factors such as differences in ability, school and gender -more details on the statistical analysis can be found in Ashton et al (2005).…”
Section: Delivery Mediummentioning
confidence: 99%